INDONESIAN EFL STUDENTS’ ATTITUDE TOWARD LEARNING ENGLISH OF ISLAMIC JUNIOR HIGH SCHOOL - Ardila, Istiqamah (STIT Ibnu Rusyd Tanah Grogot, 2022)
Attitude in one of the students’ factor that influence their performance in learning English. It shows the students positive or negative behaviour when attending to English class. This study aims to find out students’ attitudes toward learning English of Islamic Junior School that divided into three categories: behavior, cognitive, and affective. A survey research design was employed using questionnaire as the key instrument. 125 students of eight grade in Islamic Junior High School 2 Amuntai, Hulu Sungai Utara Regency, were invited to fill the questionnaire. The result revealed that students have positive attitude (M = 3.50) from behavior aspect (M = 3.66), cognitive aspect (M = 3.58), and affective aspect (M = 3.36). The finding also showed that students have most positive attitude on behavior aspect, and they tend to be neutral on affective aspect. It indicates that overall the position of students’ attitude is more to positive ways.